You can't stop the revolution: community disorder and social ties in post-Ferguson America - Boyles, Andrea S. (University of California Press, 2019)
Between a rock and a hard place : the (re)construction of blackness and identity politics -- (Dis)order and informal social ties in the United States -- "A change gotta come" : informal integration -- Making black lives matter -- "We are in a state of [mo] emergency" -- [No] conclusion and discussions.